Pratiques et lieux du e-commerce alimentaire - Nora Mareï; Anne Aguiléra; Leslie Belton-Chevallier; Corinne Blanquart; Saskia Seidel (Netcom)
E-commerce is widespread in France. If cultural products, clothing and electrical goods are now frequently bought on line, grocery purchases on the Internet have remained a niche activity despite significant growth over the last few years. The range of grocery products that can be bought on the Internet has shown an increase as have delivery and collection methods. In particular, the pick-up point has become a strong alternative to home delivery where logistical constraints make it a fragile and increasingly specific model. Through analysis of the forms of food e-commerce in France and their modalities in terms of reorganisation of logistical chains and consumer mobility, we propose to shed light on the territorial issues linked to these new purchasing practices.